Dampak Program Gerakan Pakan Ikan Mandiri (GERPARI) terhadap Kesejahteraan Petani Ikan di Kelurahan Jembatan Emas Kecamatan Pemayung Kabupaten Batang Hari - Asmaida Asmaida; Rogayah Rogayah (Jurnal Ilmiah Universitas Batanghari Jambi, 2019)
GERPARI Program through giving capital and fish feeding machine to fish farming farmers in Kelurahan Mas Bridge sub-district, Batang Hari District is expected to provide space to farmers to be able to realize the welfare of farmers In accordance with the National Medium Term Development Plan (RPJMN) III. Therefore, it is necessary to see the success rate by evaluating and reviewing the program using welfare indicators according to the Central Statistic Agency (BPS) 2015. This research aims (1) describing the welfare condition of farmers of the GERPARI Program in the village of Bridge Mas Pemayung District of Batang Hari, and (2) analyzing the impact of the GERPARI Program on changes in welfare conditions Farmers. The research method is a survey method using questionnaires. Number of samples as many as 25 farmer program recipients. Descriptive analysis is used to obtain an overview of the welfare level of farmers of the GERPARI Program in Jembatan Emas Village using welfare indicators according to BPS, 2015. The Wilcoxon test was used to analyse the impact of the GERPARI Program on the welfare of farmers in Jembatan Emas village. The results of the study showed (1) the welfare level of farmer households of GERPARI Program before receiving the low-category program of 88% and medium category as much as 12%, after receiving the welfare level program of farmers Increased to medium category as much as 44% and with high category as much as 56%. The average level of farmer welfare based on revenue indicators, health, education, levels and consumption patterns, and housing and environment before accepting the program belongs to the low category, while the after receive the program, family consumption standards and patterns, as well as residential and environmental prosperity levels belong to the medium category, while family health and education belong to the high category. (2) The assistance of the program of GERPARI that received fish farming farmers in the Kelurahan Mas Bridge Sub-district of Batang Hari District gave a significant change to the improvement of household welfare of farmers.